Tailoring Terpesomes and Leciplex for the Effective Ocular Conveyance of Moxifloxacin Hydrochloride (Comparative Assessment): In-vitro, Ex-vivo, and In-vivo Evaluation - Albash R (Dove Medical Press, 2021)
Rofida Albash,1 Menna M Abdellatif,2 Mariam Hassan,3 Noha M Badawi4 1Department of Pharmaceutics, College of Pharmaceutical Sciences and Drug Manufacturing, Misr University for Science and Technology, Giza, Egypt; 2Department of Industrial Pharmacy, College of Pharmaceutical Sciences and Drug Manufacturing, Misr University for Science and Technology, Giza, Egypt; 3Department of Microbiology and Immunology, Faculty of Pharmacy, Cairo University, Cairo, 11562, Egypt; 4Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, The British University in Egypt, Cairo, EgyptCorrespondence: Mariam HassanDepartment of Microbiology and Immunology, Faculty of Pharmacy, Cairo University, Kasr El-Aini Street, Cairo, 11562, EgyptTel +20(122)3376326Email mariam.hassan@pharma.cu.edu.egAim: To compare the ability of both terpesomes (TPs) and leciplex (LPs) loaded moxifloxacin hydrochloride (MOX) for enhancing ocular drug conveyance.Methods: Two separate 21 .31 full-factorial trials were established to determine the influence of multiple variables upon nanovesicles properties and select the optimized formulae using Design Expert® software. The thin-film hydration method was used to formulate TPs, while the single-step procedure was used for LPs. All formulae were characterized for their entrapment efficiency percent (EE%), particle size distribution (PS), polydispersity index (PDI), and zeta potential (ZP). Then, the optimized formulae were selected, evaluated, and compared for additional assessments.Results: The optimized formulae TP4 and LP1 showed EE% of 84.14± 0.21 and 78.47± 0.17%, PS of 578.65± 5.65 and 102.41± 3.39 nm, PDI of 0.56± 0.04 and 0.28± 0.01, ZP of − 12.50± 0.30 and 32.50± 0.50 mV, respectively. Further, LP1 showed enhanced corneal permeation across cow cornea compared to MOX solution and TP4. Besides, confocal laser scanning microscopy assessment viewed valuable infiltration from the fluoro-labeled LP through corneal layers compared to TP. LP1 showed spherical morphology and, its ability to adhere to mucus membranes was justified. Further, LP1 showed superiority over MOX solution in biofilm inhibition and eradication in addition to the treatment of infected mice with methicillin-resistant Staphylococcus aureus without any inflammatory response. Finally, the histopathological study verified the harmlessness and biocompatibility of the assembled LPs.Conclusion: The gained outcomes confirmed the capability of utilizing LPs as a successful nanovesicle for the ocular conveyance of MOX over TPs and MOX solution.Keywords: biofilm, confocal laser microscope, moxifloxacin hydrochloride, MRSA, leciplex, ocular drug conveyance, terpesomes